THARÎQATU TADRÎSI DINAMINAFSÎ (PSYCHODYNAMIC) WA TATHBÎQUHA FÎ TA’LÎMÎ MAHÂRATIL KALÂMI LI AT THULLÂBI JÂMIAH - Suaidi Suaidi; Dony Handriawan (Universitas Islam Negeri Mataram, 2021)
This research departs from the problem of teaching speaking skills for students ofthe Hamzanwadi Islamic Institute NWDI Pancor. This problem is caused by the factthat there are still teachers who teach speaking skills using reading, translation, andunderstanding nahwiyah rules, and neglecting appropriate and effective speakingskills teaching strategies, such as teaching strategies using innovative and effectivepsychodynamic methods. This study aims to describe psychodynamic strategies inteaching speaking skills for IAI Hamzanwadi NWDI Pancor students. This researchis a case study research with a qualitative approach. The results of this study arepsychodynamic teaching strategies to improve speaking skills of IAI HamzanwadiNWDI Pancor students by instilling motivation, increasing vocabulary andconcocting it as needed, students teaching it to other students, and doing things thatsupport teaching success and avoid things that hinder it. learning success. The roleand benefits of psychodynamic strategies in improving speaking skills are thatstudents have high enthusiasm in learning to speak, perceive that speaking Arabic iseasy and fun, vocabulary is increasing and speaking style continues to develop, themore effective the learning of speaking skills, speaking fluently is. fluent and clear,have integrative motivation, perform productive performance and apply a receptivelearning attitude.